Effect of nitrogen and phosphorus on growth and seed yield of French bean (Bangladesh Journal of Agricultural Research, 2016)
Field experiments were conducted during rabi (winter) seasons of 2010-11 and 2011-12 at the Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur to study the effects of nitrogen and phosphorus on growth, dry matter production and yield of French bean. A randomized complete block design was followed with 10 combinations of N (0,50, 100, 150 and 200) and P (0,22, 33, 44 and 55) kg ha-1 along with a blanket dose of control. All the treatments showed the maximum leaf area index (LAI) at 65 days after sowing (DAS). All the treatments showed the maximum total dry matter production, crop growth rate and net assimilation rate at harvest and at 55-65 DAS, respectively in both the years. LAI, dry matter production, CGR, NAR and seed yield significantly increased with the increase in nitrogen and phosphorus level upto 150 kg N and 44 P kg ha-1 , respectively. Similar trend was followed in maximum number of pods (9.45) and seed yield (1563.33 kg ha-1). The treatment comprises with 150 kg N and 44 P Kg ha-1 gave the highest seed yield which was 51.40 and 54.30 % higher than control plots.Bangladesh J. Agril. Res. 41(4): 759-772, December 2016